Ambulatory electrocardiographic monitoring in patients with Fabry disease: study design and cohort characterization - E. V. Kotelnikova; V. N. Senchikhin; T. P. Lipchanskaya (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To develop study design and analyze the characteristics of a cohort of patients with cardiac manifestations of Fabry disease (FD) in order to study the possibilities of electrocardiography (ECG) telemonitoring for screening for cardiac arrhythmias (CA), requiring a change in therapeutic tactics.Material and methods. This prospective cohort study included 11 patients (8 men and 3 women) with documented FD, with cardiac complaints and ECG signs of heart involvement. For ECG telemonitoring, non-invasive digital event recorders ECG Dongle (Nordavind-Dubna, Russia) were used. Primary endpoint was registration of CA requiring a change in therapeutic tactics (implantation of a pacemaker/defibrillator-cardioverter/prescribing anticoagulants). Secondary endpoint was dynamics of monitored parameters for operational correction of the therapeutic regimen.Results. The cohort of patients is predominantly male (73/27%; mean age, 41±13,7 years). At the time of inclusion, 8 (73%) patients received enzyme replacement therapy for 4-73 months. Most patients are active Internet users, are aware of telemedicine possibilities and are interested in remote monitoring. The main complaints were related to cardiac function interruptions, palpitations, and chest discomfort. Left ventricular hypertrophy was diagnosed on ECG in 7 (64%) patients. Echocardiography revealed symmetrical left ventricular hypertrophy in 5 patients, asymmetric interventricular septal hypertrophy in 2 patients. Other echocardiographic abnormalities included valvular heart disease (mitral and tricuspid valve prolapse with mitral and tricuspid regurgitation, presence of supplemental chords) and aortic root dilatation. Initially, the ECG was dominated by sinus rhythm (n=10); 1 patient had documented ventricular tachycardia, 4 patients had single and coupled ventricular premature contractions; supraventricular tachycardia and premature contractions in 2 patients. Four patients had a PR interval shortening without signs of accessory pathways, 1 patient — Wolff-Parkinson-White syndrome, 1 patient — prolonged QTc interval.Conclusion. For effective management of FD, additional multicenter studies are required to develop algorithms for making tactical decisions in the process of cardiac monitoring, taking into account the characteristics of the cardiovascular manifestations of this disease. The article proposes a technology for telemedicine cardiac monitoring using ECG event recorders for outpatient CA screening.